The Emergence of Mind: Personal Knowledge and Connectionism. - Bocharova, Jean (Tradition & Discovery, 2015)
At the end of Personal Knowledge, Polanyi discusses human development, arguing for a view of the human person as emerging out of but not constituted by its material substrate. As part of this view, he argues that the human person can never be likened to a computer, an inference machine, or a neural model because all are based in formalized processes of automation, processes that cannot account for the contribution of unformalizable, tacit knowing. This paper revisits Polanyi's discussion of the emergence of consciousness and his rejection of neural models in light of recent developments in connectionism. Connectionist neural modeling proposes an emergentist account of brain structure and, in many ways, is compatible with Polanyi's philosophy, even if it ultimately neglects questions of meaning.